Ion homeostasis in the regulation of intracellular pH and volume of human erythrocytes - О. І. Доценко; Г. В. Тарадіна (Біофізичний вісник)
Background: Cell volume maintenance by regulating the water and ion content is crucial for the survival and functional fullness of human erythrocytes. However, cells are incredibly complex systems with numerous, often competing, reactions occurring simultaneously. Hence, anticipating the overall behavior of the system or acquiring a new understanding of how the subcomponents of the system interact might pose a considerable challenge in the absence of employing mathematical modeling methods.